Strength Properties of the Heat-Resistant Inconel 718 Superalloy Additively Manufactured by Direct Laser Deposition Method under Shock Compression - Andrey S. Savinykh; Gennady V. Garkushin; Sergey V. Razorenov; Svetlana A. Atroshenko; Olga G. Klimova-Korsmik; Nikita G. Kislov (Metals, 2022)
By recording and analyzing complete wave profiles using the VISAR laser interferometer, measurements of the Hugoniot elastic limit and critical fracture stresses were carried out under the spalling conditions of the heat-resistant Inconel 718 alloy, additively manufactured by direct laser deposition, at shockwave loading up to ~6.5 GPa using a light-gas gun. For comparison, similar experiments were performed with the Inconel 718 alloy made by the traditional method of vacuum induction melting. The process of the delay of an elastic compression wave during its propagation through the sample and the dependence of the spall strength on the strain before fracture in the range 105–106 s−1 were investigated. To identify the anisotropy of the strength properties of the material under study, two series of experiments were carried out on loading additively manufactured samples along and perpendicular to the direction of the deposition. The measurements performed showed that the additively manufactured Inconel 718 alloy demonstrates weak anisotropy of strength properties for both the initial and thermal-treated samples. The thermal treatment leads to a noticeable increase in the Hugoniot elastic limit and the spall strength of the samples at low strain rates. For all types of samples, there is an increase in the spall strength with an increase in the strain rate. The spall strength measured for the cast alloy practically coincides with the strength of the as-received additive alloy and is noticeably lower than the strength of the thermal-treated additive alloy over the entire range of the strain rates. The process of the decay of the elastic precursor in the cast alloy occurs much faster than in the additive one, and the minimum values of the Hugoniot elastic limit are measured for thick samples in the cast alloy.